Body Image Disturbance in Acromegaly Patients Compared to Nonfunctioning Pituitary Adenoma Patients and Controls - Helen M. Conaglen; Dennis de Jong; Veronica Crawford; Marianne S. Elston; John V. Conaglen (International Journal of Endocrinology)
Purpose. Excess growth hormone secretion in adults results in acromegaly, a condition in which multiple physical changes occur including bony and soft tissue overgrowth. Over time these changes can markedly alter a person’s appearance. The aim of this study was to compare body image disturbance in patients with acromegaly to those with nonfunctioning pituitary adenomas (NFAs) and controls and assess the impact of obesity in these groups. Methods. A cross-sectional survey including quality of life, body image disturbance, anxiety and depression measures, growth hormone, and BMI measurement was carried out. Results. The groups did not differ with respect to body image disturbance. However separate analysis of obese participants demonstrated relationships between mood scales, body image disturbance, and pain issues, particularly for acromegaly patients. Conclusions. While the primary hypothesis that acromegaly might be associated with body image disturbance was not borne out, we have shown that obesity together with acromegaly and NFA can be associated with body image issues, suggesting that BMI rather than primary diagnosis might better indicate whether patients might experience body image disturbance problems.